2016
DOI: 10.1089/cell.2015.0051
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Enhances Direct Reprogramming of Mouse Fibroblasts to Cardiomyocyte-Like Cells

Abstract: Recent work has shown that mouse and human fibroblasts can be reprogrammed to cardiomyocyte-like cells with a combination of transcription factors. Current research has focused on improving the efficiency and mechanisms for fibroblast reprogramming. Previously, it has been reported that hypoxia enhances fibroblast cell reprogramming to pluripotent stem cells. In this study, we observed that 6 h of hypoxic conditions (2% oxygen) on newborn mouse dermal fibroblasts can improve the efficiency of reprogramming to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Wang et al (126) showed that hypoxic preconditioning of mouse neonatal tail fibroblasts at 2% O 2 for 6 h increased the frequency of GMT-induced aMHC + iCMs .10-fold to Similarly, Yoo et al (113) applied nanopatterned, gelatin-coated, polyurethane acrylate substrates to increase efficiency and speed of GMT-induced cardiac conversion in mouse fibroblasts. Mechanistically, nanotopographic cues enhanced mechanotransduction through up-regulation of focal adhesion kinase and its target genes and led to epigenetic repatterning through accumulation of permissive H3K4me3 histone marks at gene loci known to be active in CMs.…”
Section: Using Chemically Defined Serum-free Culture Conditionsmentioning
confidence: 99%
“…Wang et al (126) showed that hypoxic preconditioning of mouse neonatal tail fibroblasts at 2% O 2 for 6 h increased the frequency of GMT-induced aMHC + iCMs .10-fold to Similarly, Yoo et al (113) applied nanopatterned, gelatin-coated, polyurethane acrylate substrates to increase efficiency and speed of GMT-induced cardiac conversion in mouse fibroblasts. Mechanistically, nanotopographic cues enhanced mechanotransduction through up-regulation of focal adhesion kinase and its target genes and led to epigenetic repatterning through accumulation of permissive H3K4me3 histone marks at gene loci known to be active in CMs.…”
Section: Using Chemically Defined Serum-free Culture Conditionsmentioning
confidence: 99%
“…In comparison with normoxic conditions, HIF-1α expression slightly increased during the two first weeks and then returned to normal levels. Although these researchers did not achieve fully reprogrammed functional iCMs, their study shed light on the effect of microenvironment factors on cardiac reprogramming [46]. Very recently, it has been demonstrated that hypoxia increases genomewide epigenetic bivalency (H3K4me3 and H3K27me3) in breast cancer [84].…”
Section: Hypoxiamentioning
confidence: 99%
“…According to the various important roles of oxygen in CM generation and function, oxygen appeared to affect direct cardiac reprogramming. Recently, Wang et al reported that a short term pretreatment of neonatal mouse dermal fibroblasts with low levels (2%) of oxygen for 6 h improved the efficiency of GMT-based cardiac reprogramming ( Table 2) [46]. They showed that hypoxic pretreatment for 6 h increased the efficiency of Myh6+ and cTnI+ cell generation by 10and 2.0-fold, respectively.…”
Section: Hypoxiamentioning
confidence: 99%
“…It has been reported that hypoxic pretreatment of newborn mouse dermal fibroblasts for 6 h can improve the efficiency of iCM reprogramming [41]. Especially, a two-fold increase in cardiac troponin I (cTnI) expression and cTnt has been observed.…”
Section: Cardiac Reprogramming Involves Key Processes In Cardiogenmentioning
confidence: 99%